2007
DOI: 10.1136/bjo.2007.115162
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of retinal detachment after macular surgery: a retrospective study of 634 cases

Abstract: Aims: To evaluate the rate of retinal detachment after macular surgery. Methods: A retrospective non-randomised study of 634 macular surgery procedures was undertaken in two academic centres. Idiopathic macular hole (IMH) surgery (n = 272) and epiretinal membrane (ERM) surgery (n = 362) were performed between 2000 and 2003. We noted the anatomical and functional results of these procedures and we studied serious complications excluding cataract. Results: Minimum follow up was 1 year. No retinal detachment (RD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 28 publications
(19 reference statements)
3
37
2
3
Order By: Relevance
“…Rates of complications in this study were similar to those of previously published articles. 5 It would therefore be of economic and symptomatic benefit to the patient if a combined procedure was undertaken as the rates of cataract progression are high following PPV. 19,20 In conclusion, this study shows improvement in VA after PPV and ERM removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of complications in this study were similar to those of previously published articles. 5 It would therefore be of economic and symptomatic benefit to the patient if a combined procedure was undertaken as the rates of cataract progression are high following PPV. 19,20 In conclusion, this study shows improvement in VA after PPV and ERM removal.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery can lead to complications, which can worsen vision and in some cases cause complete visual loss in the operated eye. 5 In addition, many ERMs are asymptomatic and non-progressive. Population studies have shown the rate of progression of ERMs to be between 16 and 33%.…”
Section: Introductionmentioning
confidence: 99%
“…The breaks located in the superior quadrants, particularly in the quadrant near the surgeon's dominant hand, are considered sclerotomy-related breaks. 1,3,6,12,13 On the other hand, an IPVD is thought to be an important etiology when the breaks are located in the inferior quadrants. 2,3,5 Two of three (66.7%) retinal breaks in the PPH group were identified in the superior quadrants, near the sclerotomy sites, suggesting the etiology of these breaks could be sclerotomy-related rather than IPVD-related.…”
Section: Discussionmentioning
confidence: 99%
“…Given the position and direction of the vitreous cutter in conventional vitrectomy, some degree of perpendicular traction to the vitreous base cannot be avoided (Figure 1-A3). Considering the similar propensity for the incidence of PVD-related retinal break in macular surgery despite the evolution of the vitrectomy machine, 1,3,4,6,[8][9][10][11][12] the effect of increasing cut velocity may be limited. Some degree of artificial vitreous traction seems to be inevitable during peripheral vitreous removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation